2019
DOI: 10.31157/an.v24i4.189
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericitoma / tumor fibroso solitario: presentación de caso y revisión de la literatura

Abstract: El Hemangiopericitoma/Tumor Fibroso Solitario meníngeo es un tumor raro del sistema nervioso central que presenta una alta tasa de recidiva local y de metástasis extracraneal. Debido a su rareza, hay poco material estadístico para determinar el mejor tratamiento, pero se sabe que responden mejor a una resección total. Se revisa el tema debido al reciente cambio de nomenclatura y clasificación de este tipo de tumor y la presentación de un caso y su manejo. Posteriormente, se hace una revisión de la literatura p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…14,15 In 2007 the World Health Organization differentiated SFT and hemangiopericytomas (HPC) as two different entities, but on 2016 it was demonstrated that both shared a genetic mutation in which a 12q13 inversion occurred that merged NAB2 and STAT6 genes, generating a nuclear expression of STAT6 identifiable by immunologic studies, so nowadays both entities are recognized as one, the Solitary Fibrous Tumor / hemangiopericytoma (SFT/HPC). 16 As described before, SFT are rare, representing just 1-2% of all soft tissue tumors, and it has an incidence of 0, 35 for each 100.000 habitants. 10,12 Because of their slow growth, a parapharyngeal location can become symptomatic when the tumor reaches up to 2,5cms.…”
Section: Discussionmentioning
confidence: 86%
“…14,15 In 2007 the World Health Organization differentiated SFT and hemangiopericytomas (HPC) as two different entities, but on 2016 it was demonstrated that both shared a genetic mutation in which a 12q13 inversion occurred that merged NAB2 and STAT6 genes, generating a nuclear expression of STAT6 identifiable by immunologic studies, so nowadays both entities are recognized as one, the Solitary Fibrous Tumor / hemangiopericytoma (SFT/HPC). 16 As described before, SFT are rare, representing just 1-2% of all soft tissue tumors, and it has an incidence of 0, 35 for each 100.000 habitants. 10,12 Because of their slow growth, a parapharyngeal location can become symptomatic when the tumor reaches up to 2,5cms.…”
Section: Discussionmentioning
confidence: 86%
“…En 2007 la OMS clasificaba a los hemangiopericitomas y al TFS como entidades diferentes, pero se mostró recientemente que ambos comparten una inversión en 12q13 que fusiona a los genes NAB2 y STAT6, causando una expresión nuclear de STAT6 que puede ser detectada por inmunohistoquímica. Debido a esto, se consideran parte del mismo espectro tumoral 16 .…”
Section: Discussionunclassified